Identification of Novel Mutations in Chinese Infants With Citrullinemia - Cheng, Zhi; He, Xiwen; Zou, Fa; Xu, Zhen-E; Li, Chun; Liu, Hao; Miao, Jingkun (Frontiers in Genetics, 2022)
Citrullinemia is a rare autosomal recessive disorder characterized by elevated concentrations of citrulline in the blood resulting from malfunction of the urea cycle. It is categorized into two types, types I and II, which are caused by argininosuccinate synthase 1 (ASS1) and citrin (SLC25A13) gene mutations, respectively. In this study, we performed genetic analysis on nine Chinese infants with citrullinemia using next-generation sequencing, which identified a novel mutation (p.Leu313Met) and a rare mutation (p.Thr323Ile, rs1250895424) of ASS1. We also found a novel splicing mutation of SLC25A13: c.1311+4_+7del. Functional analysis of the ASS1 missense mutations showed that both significantly impaired the enzyme activity of ASS1, with the p.Thr323Ile mutation clearly affecting the interaction between ASS1 and protein arginine methyltransferase 7 (PRMT7). These findings expand the mutational spectrum of ASS1 and SLC25A13, and further our understanding of the molecular genetic mechanism of citrullinemia in the Chinese population.